Significance of biogas production in Hungary - Kith, Károly (Acta Agraria Debreceniensis, 2013)
It is known that the quantity of fossil energy sources are rapidly reducing, therefore it is necessary to determine a new direction which has to point directly to renewable energy sources. Increasingly comes into view the agriculture’s energy producing nature next to it’s traditional food producing one. The enviromental protection is connected to the energy production by the ultilization of biomass for energy purposes, within the biogas production has an emphasized importance. Quasi every organic material can be used in biogas production, such as: food processing by-products, manure, sewage sludge, hoousehold waste.